2017
DOI: 10.1007/s10827-017-0641-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionic currents influencing spontaneous firing and pacemaker frequency in dopamine neurons of the ventrolateral periaqueductal gray and dorsal raphe nucleus (vlPAG/DRN): A voltage-clamp and computational modelling study

Abstract: Dopamine (DA) neurons of the ventrolateral periaqueductal gray (vlPAG) and dorsal raphe nucleus (DRN) fire spontaneous action potentials (APs) at slow, regular patterns in vitro but a detailed account of their intrinsic membrane properties responsible for spontaneous firing is currently lacking. To resolve this, we performed a voltage-clamp electrophysiological study in brain slices to describe their major ionic currents and then constructed a computer model and used simulations to understand the mechanisms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
(223 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that the magnitude of I h in electrically excitable cells might greatly influence the rising phase of pacemaker potential or abrupt spike depolarizations [ 24 , 34 , 44 , 47 , 48 ]. Thus, next, we intended to determine how HNK exerted any perturbations on the deactivating I h in response to the upsloping ramp pulse from −120 to −40 mV with varying durations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that the magnitude of I h in electrically excitable cells might greatly influence the rising phase of pacemaker potential or abrupt spike depolarizations [ 24 , 34 , 44 , 47 , 48 ]. Thus, next, we intended to determine how HNK exerted any perturbations on the deactivating I h in response to the upsloping ramp pulse from −120 to −40 mV with varying durations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the magnitude of I h in electrically excitable cells might greatly influence the rising phase of pacemaker potential or abrupt spike depolarizations [24,34,44,47,48].…”
Section: Effect Of Hnk On Deactivating I H Elicited Upon Return To Mementioning
confidence: 99%
See 1 more Smart Citation
“…Barium currents were recorded as a proxy for calcium currents to get better signal-to-noise ratio and to minimize inactivation (Dougalis et al, 2017; Hille, 2001), and were recorded in the presence of compounds to block sodium and potassium currents in modified oxygenated ACSF with composition (in mM): 95 NaCl, 2.5 KCl, 10 HEPES, 1.25 NaH2PO4, 1 MgCl2, 20 glucose, 0.5 BaCl2, 4 4-AP, 20 TEA and 1μm TTX (osmolarity 290, pH 7.35). Neurons were held −70 mV, hyperpolarized to −110 mV, and then depolarized in 5 mV increments to 30 mV.…”
Section: Som Experimental Procedures and Methodsmentioning
confidence: 99%
“…Another component of the midbrain dopamine system—the DRN dopamine neurons—also exhibits acute isolation‐induced adaptations. These dopamine neurons were historically considered a caudal extension of the VTA, but accumulating evidence has revealed distinct downstream projections and functional roles . In adult male mice, 24‐h social isolation potentiated glutamatergic synapses onto DRN dopamine neurons, and also heightened their activity in vivo in response to a novel mouse .…”
Section: Homeostatic Response To Social Deficit: Engaging Social Motimentioning
confidence: 99%